Naturally overused : an analysis of health claims on "healthy" supermarket food products with an emphasis on the "natural" angle - Chua, Joanne Wanlin (2010)
This study examined the use of healthful claims on food packaging in view of the new trend of marketing food as natural. A content analysis of 328 food products in Singapore revealed the prevalent use of the natural claim as well as visual communication images that evoke the same connotations of naturalness. A closer check revealed that a great number of products with natural claims were found to contain additives. Study 2 followed with an online experiment to examine whether extrinsic cues such as the claim “All Natural” and an external seal can effectively influence consumers’ perception of the product’s nutritional attributes. Results showed that the “All Natural” claim does effectively influence consumers’ perception of the product and that this claim also interacts with the seal. This suggests that consumers commonly use such extrinsic cues for healthful decision-making. Implications of the findings are discussed.